Cutaneous metastases of lung adenocarcinoma: a case report. - Pereira, Patricia M; Barrigoto, Cleide; Amorim, Helena (European Journal of Oncology and Environmental Health, 2019)
Cutaneous metastases from lung carcinoma are rare and have ominous prognosis. They are an important finding and are not often the first sign leading to diagnosis. We reported a case in which a 52-year-old male, smoker, initially presented with rapidly growing skin nodules on his back and right thigh, without any pulmonary complaints. Biopsy of the skin nodules revealed metastatic adenocarcinoma consistent with primary lung origin. Computed tomography showed an expansive process on the upper lobe of left lung with atypical characteristics suspicious of primary site. Abdominal and pelvic CT scan showed disseminated bone metastases. In a multidisciplinary discussion, it was considered that there is no indication for chemotherapy or radiotherapy due to the rapid clinical worsening of the patient. He received palliative treatment and died 5 weeks after diagnosis of his metastatic lung cancer. We are presenting a rare case of lung adenocarcinoma with skin metastases, which was simultaneously diagnosed. A high index of suspicion is necessary for the early detection of cutaneous metastases from lung tumours, especially if there is history of smoking or lung cancer.